Extracorporeal membrane oxygenation for Chinese neonates with severe respiratory and cardiac failure - Xiao-Juan Zhang; Ying-Yue Liu; Hui Wang; Xiao-Yang Hong (Journal of Cardiothoracic Surgery)
Abstract Objective We aimed to outline the experience with extracorporeal membrane oxygenation (ECMO) for respiratory and cardiac failure in neonates in our institution and compare our results with those from other countries. Method The clinical data of 28 neonates who required ECMO assistance were studied retrospectively. Results A total of 28 neonates underwent support with veno-arterial ECMO, including 14 cardiac support and 14 respiratory support. The neonates with a median age of 5 days (1–28 days) and a median weight of 3.3 kg (2.4–4.2 kg). Of these neonates, 4 were female, and 24 were male. Among the neonates. For neonates requiring ECMO support for cardiac conditions, 9 survived, resulting in a 64% survival rate. In contrast, for those requiring ECMO support for respiratory conditions, 6 survived, indicating a 42% survival rate. The survivors exhibited a significant reduction in lactic acid levels within the first 24 h. In the 15 successful weaning neonates, four neonates died at the end of the study; one was for the cardiac function failure; two were for the respiratory failure; one was given up for Bipedal necrosis; the other 11 neonates were successful discharge. Notably, two neonates underwent ECMO ventilation in the prone position without experiencing any complications. Conclusion The utilization of ECMO support in neonates experiencing severe respiratory and cardiac failure efficiently improves cardiopulmonary function and significantly reduces mortality rates among critically ill neonates. The neonates with a respiratory indication in our study have a lower survival rate than other reported in the literature. Monitoring the trend in lactate levels following ECMO support proves valuable in estimating the prognosis of affected children.